The Auditor-Firm Conflict of Interests: A Comment. - Aranya, Nissim; Sarell, Moshe (The Accounting Review, 1975)
This article presents comments of the author on the paper "The Auditor-Firm Conflict of Interests: Its Implications for Independence," by A. Goldman and B. Barlev that was published in the October 1974 of the periodical "The Accounting Review." In their paper, the authors attempted to analyze the set of factors affecting the relationships between auditors and firms, and in particular the problem of auditors' independence. In doing so, they touch upon areas of sociological analysis which have been developed in the past few decades, especially the sociology of professions. Their use of the relevant literature, however, leaves much to be desired. The authors ignore a basic distinction between interpersonal and institutional autonomy-problems. Scholar E. Friedson refers to it as private interaction versus public interaction, that is, between the micro-level and macro-level phenomena. The autonomy of a particular auditor vis-a-vis his client is a product of a set of factors affecting their specific mode of interaction, but the autonomy of the profession of public accountancy is determined by collective variables, not reducible to interpersonal relationships.